Selective isolation of agents of chromoblastomycosis from insect-associated environmental sources - Lima, Bruna Jacomel Favoreto de Souza (2020)
Chromoblastomycosis is a neglected disease characterized by cutaneous, subcutaneous or disseminated lesions. It is considered an occupational infectious disease that affects mostly rural workers exposed to contaminated soil and vegetal matter. Lesions mostly arise after a traumatic inoculation of herpotrichiellaceous fungi from the Chaetothyriales order. However, the environmental niche of the agents of the disease remains obscure. Its association with insects has been predicted in a few studies. Therefore, the present work aimed to analyze if social insects, specifically ants, bees, and termites, provide a suitable habitat for the fungi concerned. The mineral oil flotation method was used to isolate the microorganisms. Nine isolates were recovered and phylogenetic analysis identified two strains as potential agents of chromoblastomycosis, i.e., Fonsecaea pedrosoi CMRP 3076, obtained from a termite nest (n = 1) and Rhinocladiella similis CMRP 3079 from an ant exoskeleton (n = 1). In addition, we also identified Fonsecaea brasiliensis CMRP 3445 from termites (n = 1), Exophiala xenobiotica CMRP 3077 from ant exoskeleton (n = 1), Cyphellophoraceae CMRP 3103 from bees (n = 1), Cladosporium sp. CMRP 3119 from bees (n = 1), Hawksworthiomyces sp. CMRP 3102 from termites (n = 1), and Cryptendoxyla sp. from termites (n = 2). The environmental isolate of F. pedrosoi CMRP 3076 was tested in two animal models, Tenebrio molitor and Wistar rat, for its pathogenic potential with fungal retention in T. molitor tissue. In the Wistar rat, the cells resembling muriform cells were observed 30 d after inoculation.